Pewne Metody Wyrównywania Naprężeń Głównych w Płaskich Ośrodka Sprężystych - Holnicki-Szulc, J. (Engineering Transactions, 1971)
In the paper the problem of compensating the main stresses in a plane elastic medium by changes of the thickness and of the field of body forces is considered. This problem was formulated by Z. Wasiutyński in paper [3].In this paper the method of solving the problem is given assuming two equations of equilibrium as initial, and the equation of continuity of deformations with consideration of the condition of compensation of the main stresses [3]. The basic part of the work is the method of solving the partial differential equation describing the slope of the trajectory of the main stresses. For this purpose the method of characteristics [l and 5] was applied. In the paper the boundary conditions of the problem are also given, and the numerical method of its solution is given for the case of introduction of a certain constructional condition (e.g., constant thickness of the medium).